ZEB1 Mediates Bone Marrow Mesenchymal Stem Cell Osteogenic Differentiation Partly via Wnt/β-Catenin Signaling - Xu, Cuidi; Shi, Hongli; Jiang, Xin; Fan, Yongqian; Huang, Donghui; Qi, Xinming; Cheng, Qun (Frontiers in Molecular Biosciences, 2021)
Abstract ZEB1 is zinc-finger transcription factors best known for its role in promoting epithelial-mesenchymal transition, which is also related to osteogenesis. In present study, ZEB1 was investigated for its involvement in osteoblasts commitment of BMSCs. ZEB1 was confirmed its expression decreased following osteogenic differentiation. In vitro, Silencing of ZEB1 in BMSCs promoted osteogenic activity and mineralization, vice versa. The increase of osteogenic differentiation induced by si-ZEB1 could be partly rescued by inhibitor of Wnt/β-catenin (si-β-catenin). In vivo, knockdown of ZEB1 in BMSCs inhibited the rapid bone loss of OVX mice. It was also proven that the expression of ZEB1 negatively associated with bone mass and bone formation in postmenopausal patients. In conclusion, ZEB1 was an essential transcription factor in BMSCs differentiation and may serve as a potential anabolic strategy for treatment and prevention of postmenopausal osteoporosis.